Effect of ergothioneine on tissue metabolism in middle-aged and aged mice - CHEN Haoran, WANG Fang, MA Yanni, YU Jia, WANG Lin (Jichu yixue yu linchuang)
Objective To investigate the effect of ergothioneine(EGT) on tissue metabolism in middle-aged and aged mice. Methods Nine-month-old middle-aged and aged C57BL/6J mice were selected to be gavaged with EGT aqueous solution at the dose and frequency of 35 mg EGT per kg body weight every two days. The control group was gavaged with the same amount of water. Both groups were fed with EGT-free diet. After 7 weeks, the liver, kidney, and small intestine of mice were collected, and untargeted metabolomics analysis was performed using ultra-performance liquid chromatography-mass spectrometry(UHPLC-MS). The differential metabolites were selected for KEGG metabolic pathway enrichment analysis. Results Compared with the control group, the abundances of metabolites related to redox balance in liver, kidney and small intestine of middle-aged and aged mice treated with EGT did not change significantly. However, taurine and hypotaurine metabolism in liver(P＜0.01), purine metabolism in kidney(P＜0.01), and cysteine and methionine metabolism in small intestine(P＜0.001) were affected. Conclusions Non-redox-related metabolic changes in the liver, kidney and small intestine of middle-aged and aged mice by ergothioheine.